IMRT in a rare case of bilateral optic nerve glioma. Issue 1 (19th March 2021) - Singh, Rashmi; Kumar, Anup; Tudu, Rajanigandha; Raina, Payal; Munda, Praveer
Abstract: Purpose: Optic nerve glioma (OPG) is a rare tumour of children and adolescents. The treatment is challenging as it may jeopardise the visual outcome. We are reporting a case of bilateral OPG, treated with intensity-modulated radiotherapy in our department. Material and Method: An 18-year-old female presented with a gradually deteriorating vision in both eyes. A detailed clinical and ophthalmological examination was carried out. Her MRI of orbit and brain were suggestive of bilateral optic nerve glioma. She was treated with intensity-modulated radiotherapy to a total dose of 54Gy in 30 fractions over 6 weeks. Results: She well tolerated the treatment. Post radiotherapy at 8 weeks, she had stabilization of vision on clinical assessment. Conclusion: Radiotherapy using IMRT can be successfully used to treat OPG, and it checks tumour growth and prevents further deterioration.